Sparse-sampling computed tomography for detection of endoleak after endovascular aortic repair (EVAR). Issue 142 (September 2021) - Meurer, Felix; Kopp, Felix; Renz, Martin; Harder, Felix N.; Leonhardt, Yannik; Bippus, Rolf; Noël, Peter B.; Makowski, Markus R.; Sauter, Andreas P.
Highlights: With sparse sampling CT, radiation dose could be significantly reduced in clinical routine. Sparse sampling CT is a novel hardware solution with which less projection images are acquired. In the current study, a dose reduction of 75% for CTA after EVAR could be achieved. Abstract: Objectives: To evaluate sparse sampling computed tomography (SpSCT) for detection of endoleak after endovascular aortic repair (EVAR) at different dose levels in terms of subjective image criteria and diagnostic accuracy. Methods: Twenty clinically indicated computed tomography aortic angiography (CTA) scans were used to obtain simulated low-dose scans with 100%, 50%, 25%, 12.5% and 6.25% of the applicated clinical dose, resulting in five dose levels (DL). From full sampling (FS) data sets, every second (2-SpSCT) or fourth (4-SpSCT) projection was used to generate simulated sparse sampling scans. All examinations were evaluated by four blinded radiologists regarding subjective image criteria and diagnostic performance. Results: Sensitivity was higher than 93% in 4-SpSCT at the 25% DL which is the same as with FS at full dose (100% DL). High accuracies and relative high AUC-values were obtained for 2- and 4-SpSCT down to the 12.5% DL, while for FS similar values were shown down to 25% DL only. Subjective image quality was significantly higher for 4-SpSCT compared to FS at each dose level. More than 90% of all cases were rated with a high or medium confidence for FS and 2-SpSCT at the 50% DL and for 4-SpSCT at the 25% DL. At DL 25% and 12.5%, more cases showed a high confidence using 2- and 4-SpSCT compared with FS. Conclusions: Via SpSCT, a dose reduction down to a 25% dose level (mean effective dose of 1.49 mSv in the current study) for CTA is possible while maintaining high image quality and full diagnostic confidence.